2020
DOI: 10.1038/s41467-020-17128-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of seamless excision and specific targeting by piggyBac transposase

Abstract: The piggyBac DNA transposon is used widely in genome engineering applications. Unlike other transposons, its excision site can be precisely repaired without leaving footprints and it integrates specifically at TTAA tetranucleotides. We present cryo-EM structures of piggyBac transpososomes: a synaptic complex with hairpin DNA intermediates and a strand transfer complex capturing the integration step. The results show that the excised TTAA hairpin intermediate and the TTAA target adopt essentially identical conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 97 publications
8
91
0
Order By: Relevance
“…5b) (subfamily AluSx) as against the general distribution of TE classes (χ2 test p value <0.01). We can conclude that PGBD1 has lost ability to recognise itself or related sequences, consistent with its loss of the CRD 49 , this domain being key to terminal inverted repeat recognition 80 .…”
Section: Pgbd1 Genomically Does Not Recognise Piggybac-related Sequencessupporting
confidence: 62%
“…5b) (subfamily AluSx) as against the general distribution of TE classes (χ2 test p value <0.01). We can conclude that PGBD1 has lost ability to recognise itself or related sequences, consistent with its loss of the CRD 49 , this domain being key to terminal inverted repeat recognition 80 .…”
Section: Pgbd1 Genomically Does Not Recognise Piggybac-related Sequencessupporting
confidence: 62%
“…The original PB transposon has a total length of 2475 bp [ 74 ], and harbors a single open reading frame (ORF) encoding a transposase. The transposase itself is 594 aa long, and contains dimerization and DNA-binding domains, a catalytic domain including the DDD catalytic triad (positions 268, 346, and 447) interrupted by an insertion domain, an acidic N-terminal domain and cysteine-rich C-terminal domain (CRD) [ 76 ], the latter of which includes an NLS predicted to span from positions 551 to 571 [ 77 ] ( Figure 2 B). The ORF is flanked by terminal sequences containing asymmetric inverted repeats: 13-bp long TIRs separated, by 3-bp in the left and 31-bp in the right terminal sequence, from 19-bp long sub-terminal repeats critical for transposon end recognition and target for CRD binding [ 78 ], respectively.…”
Section: The Piggybac Transposon Systemmentioning
confidence: 99%
“…A large-scale survey of PBLE transposons allowed the definition of four structural groups, based on the differential organization of DNA repeats at their ends [13]. In particular, the piggyBat transposon from the bat Myotis lucifugus, which belongs to the first group, carries simple 15-bp TIRs at its ends [11], while piggyBac from T. ni and PLE-wu from the insect Spodoptera frugipeda [12], representatives of the fourth group, carry complex TIRs with multiple internal repeats and may require complex interactions for the correct conformation of their transpososome [36]. While all PBLE transposases harbor a characteristic conserved domain (PF13843, or DDE_ Tnp_1_7), which includes their catalytic site, the study by Bouallègue et al [13] has highlighted the diversity of the Cys/His motifs found in their C-terminal CRDs.…”
Section: Structure-function Variability Of the Crds Of Pble Transposases And Domesticated Pgbd Proteinsmentioning
confidence: 99%
“…a zinc finger, in which the structural cores of the two zinc ions overlap) and binds specifically to a repeated DNA sequence motif present at piggyBac transposon ends [35]. Recent cryo-electron microscopy data indicated that the PB transposase assembles as a dimer within a synaptic complex composed of two piggyBac left ends, with the two PB CRDs binding together to a single end, introducing asymmetry within the complex [36]. P. tetraurelia IESs, intriguingly, do not carry a conserved motif that may serve as a sequence-specific recognition site for Pgm and, compared with PB, the primary sequence of the Pgm CRD exhibits a different arrangement of its potentially zinc-coordinating residues [19].…”
Section: Introductionmentioning
confidence: 99%